2022
DOI: 10.1158/0008-5472.can-21-1020
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Kinase Activity of NME7 Activates Wnt/β-Catenin Signaling to Promote One-Carbon Metabolism in Hepatocellular Carcinoma

Abstract: Metabolic reprogramming by oncogenic signaling is a hallmark of cancer. Hyperactivation of Wnt/β-catenin signaling has been reported in hepatocellular carcinoma (HCC). However, the mechanisms inducing hyperactivation of Wnt/β-catenin signaling and strategies for targeting this pathway are incompletely understood. In this study, we find nucleoside diphosphate kinase 7 (NME7) to be a positive regulator of Wnt/β-catenin signaling. Upregulation of NME7 positively correlated with the clinical features of HCC. Knock… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…MTHFD2 is also a metabolic checkpoint linking purine metabolism to autoimmune responses ( Sugiura et al, 2022 ). It is highly expressed in various cancers, playing a role in metabolic remodeling and regulating of the cell cycle in the mitochondria and nucleus, respectively ( Lee et al, 2021b ; Liu et al, 2021 ; Yao et al, 2021 ; Ren et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…MTHFD2 is also a metabolic checkpoint linking purine metabolism to autoimmune responses ( Sugiura et al, 2022 ). It is highly expressed in various cancers, playing a role in metabolic remodeling and regulating of the cell cycle in the mitochondria and nucleus, respectively ( Lee et al, 2021b ; Liu et al, 2021 ; Yao et al, 2021 ; Ren et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The tissue array was obtained from Shanghai Outdo Biotech Co., Ltd. IHC staining was performed as previously described [18]. The anti-HMGCL antibody (16898-1-AP, 1:100) was obtained from Proteintech.…”
Section: Immunohistochemical (Ihc) Analysismentioning
confidence: 99%
“…The CCK-8 assay was performed as previously described [18]. Briefly, cells were seeded into a 96-well plate, with 1×10 3 cells in each well, and cultured in an incubator (37 °C, 5% CO 2 ).…”
Section: Cck-8 Assaymentioning
confidence: 99%
“…Numerous studies have shown that metabolic reprogramming plays a role in the occurrence and development of tumors as one of the typical malignant features of tumors [1][2][3][4]. During tumor evolution, metabolic pathways are reprogrammed to meet the material and energy demands of tumor growth.…”
Section: Introductionmentioning
confidence: 99%